Enhancing EFL Students’ Essay Writing Skills Through TPACK-Driven Flipped Learning: A Lesson from Lecture-Based Instruction - Nugroho Nugroho (Universitas Pendidikan Mandalika, 2026)
This study examines how TPACK-based flipped learning improves undergraduate EFL essay writing. Traditional lecture-based education has failed to address EFL students' academic essay challenges including coherence, grammatical precision, and argument organization. We employed a quasi-experimental mixed-methods approach with 60 undergraduate EFL students at a private university in Jakarta, Indonesia, randomly assigned to control or experimental groups for a 12-week intervention. The experimental group employed TPACK-based flipped learning, incorporating pre-class video lectures, online interactive quizzes, Google Docs collaborative writing, grammar-checking software, and scaffolded peer review, whereas the control group received traditional lectures. The experimental group demonstrated significant improvement across all writing skills, including coherence, grammar accuracy, and argumentation. Analysis of covariance revealed that the intervention accounted for nearly one-third of post-test performance differences, whereas the control group made minor, non-significant gains. Qualitative data revealed positive student responses: 89% reported a better understanding of essay structure, and 87% indicated significant improvement in writing skills. These findings provide EFL educators with a validated framework for meaningful technology integration into writing instruction, demonstrating that systematic TPACK implementation can transform traditional pedagogy into student-centered, collaborative learning environments. While limited to intermediate-level learners in a specific cultural context, this research offers scalable strategies for institutions seeking evidence-based approaches to enhance academic writing outcomes through purposeful technology integration.